Three representative inter and intra‐subspecific crosses reveal the genetic architecture of reproductive isolation in rice. (20th September 2017) - Li, Guangwei; Li, Xiaoting; Wang, Yuan; Mi, Jiaming; Xing, Feng; Zhang, Dahan; Dong, Qiyan; Li, Xianghua; Xiao, Jinghua; Zhang, Qifa; Ouyang, Yidan
Summary: Systematic characterization of genetic and molecular mechanisms in the formation of hybrid sterility is of fundamental importance in understanding reproductive isolation and speciation. Using ultra‐high‐density genetic maps, 43 single‐locus quantitative trait loci (QTLs) and 223 digenic interactions for embryo‐sac, pollen, and spikelet fertility are depicted from three crosses between representative varieties of japonica and two varietal groups of indica, which provide an extensive archive for investigating the genetic basis of reproductive isolation in rice. Ten newly detected single‐locus QTLs for inter‐ and intra‐subspecific fertility are identified. Three loci for embryo‐sac fertility are detected in both Nip × ZS97 and Nip × MH63 crosses, whereas QTLs for pollen fertility are not in common between the two crosses thus leading to fertility variation. Five loci responsible for fertility and segregation distortion are observed in the ZS97 × MH63 cross. The importance of two‐locus interactions on fertility are quantified in the whole genome, which identify that three types of interaction contribute to fertility reduction in the hybrid. These results construct the genetic architecture with respect to various forms of reproductive barriers in rice, which have significant implications in utilization of inter‐subspecific heterosis along with improvement in the fertility of indica–indica hybrids at single‐ and multi‐locus level. Significance Statement: Reproductive barriers in rice are widely observed phenomenon and demand an understanding for biological study of speciation and practical application to agriculture. This work provides an extensive archive for investigating the genetic basis of inter‐ and intra‐subspecific reproductive isolation in rice at the whole‐genome level, which reveals the phenotypic effects for single‐locus QTLs and allelic combinations at multi‐locus level, thus providing new strategies for our current utilization of heterosis.